Research progress on the mechanisms of endogenous neural stem cell differentiation in spinal cord injury repair - Wang, Tianwei; Han, Qing; Lv, Shi; Zhang, Li-ping; Li, Hengrui; Liu, Jian; Kuang, Jinyi; Sun, Bao-liang; Sun, Jing-yi (Frontiers in Cellular Neuroscience, 2025)
Spinal cord injury (SCI) is a devastating condition with limited self-repair capacity, resulting in long-term disabilities. Endogenous neural stem cells (eNSCs), which are present in the adult central nervous system (CNS), hold significant potential for repairing neural damage following SCI. These cells can proliferate, migrate to the injury site, and differentiate into various neural cell types, including neurons and glial cells. However, after SCI, eNSCs predominantly differentiate into astrocytes, with minimal neuronal differentiation, thereby hindering effective neural regeneration. This review summarizes the key mechanisms underlying the differentiation of eNSCs into neurons, focusing on the molecular signaling pathways that regulate their fate, including the Notch, Wnt/β-catenin, Sonic Hedgehog, and PI3K/Akt pathways. It also discusses the microenvironment’s role, including factors such as hypoxia, extracellular matrix components, and inflammatory cytokines, which influence eNSCs differentiation. The review also highlights potential therapeutic strategies to enhance eNSCs differentiation into neurons, including biomaterials and multimodal approaches that combine pharmacological, physical, and tissue engineering techniques. Despite progress in understanding eNSCs biology and signaling mechanisms, challenges remain in optimizing therapeutic strategies for SCI repair. Future research should focus on overcoming these limitations, emphasizing refining treatment timing, drug delivery systems, and the development of personalized therapies to promote effective neural regeneration and functional recovery after SCI.